A pilot study of healing critical-sized calvarial defects by LL-37-generated monoosteophils - Le, Keith; Liu, Huinan; Zhang, Chaoxing; Li, Zhuo; Olafsen, Tove; Fong, Yuman; Shively, John E.; Zhang, Zhifang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMonoosteophils, derived from LL-37-treated monocytes, are a novel type of calcifying/bone forming cells. We have shown that monoosteophils can form bone-like nodules in vitro and accelerate bone repair in a drilled femur defect model. Here, we explored the bone repair function of monoosteophils in a mouse model of critical-sized calvarial defect and the mechanism of bone nodule formation of monoosteophils in vitro.MethodsHuman monocytes were isolated from peripheral blood and differentiated into monoosteophils. Critical-sized (5 mm-diameter) calvarial defects in the parietal bone of adult male NOD/SCID mice were implanted with either 1-day untreated human monocytes, 1-day LL-37 treated human monocytes (monoosteophils), 1-day human monocytes plus hydroxyapatite nanoparticles or 1-day human monoosteophils plus hydroxyapatite nanoparticles. Micro-computed tomography (µCT) was used for assessment of bone formation in the mouse model. Alizarin Red S staining (ARS), FAM-alendronate staining, light and fluorescence microscopy, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and transmitted electron microscopy (TEM) were used to examine bone nodule formation in vitro.ResultsThe most complete healing (80%) was observed for monoosteophils plus nano-scale hydroxyapatite. The results of a dose response study (5 × 106, 2.5 × 106, 1.25 × 106 and 0.625 × 106 MOP cells) showed that monoosteophil cell counts as low as 0.625 × 106 cells were able to significantly repair the defect area over a short-term observation period of 4 weeks. Mechanistic in vitro studies using ARS and FAM-alendronate staining showed that monoosteophils form bone nodule in αMEM medium supplemented with 2.5 mM CaCl2. SEM/EDS analysis confirmed that the bone nodules consisted of phosphorus, calcium, oxygen, and sodium. Monoosteophils in culturing condition formed the unique granules in the cytoplasm consisting of phosphorus, calcium, oxygen, and sodium evidenced by SEM/EDS.DiscussionWe now demonstrate that the bone repair function of monoosteophils requires hydroxyapatite through intracellular nodule formation and monoosteophils are capable of filling in large calvarial defects in our pilot study. These observations may have important implications in facilitating the development of therapeutic applications for clinically challenging bone repairs and the understanding of pathological mineralization.